Policy Implementation of the Bus Rapid Transit System in Mataram City - Muhammad Aprian Jailani; Abdul Hakim; Suryadi Suryadi (Sekolah Pascasarjana Universitas Brawijaya, 2019)
The ministerial decree 692-2015 of Ministry of Transportation of the Republic of Indonesia regarding the Allocation of BRT of BRT Assistance have granted Mataram city that 25 BRT. The BRT is a program of Law 22 of 2009 regarding Road Traffic & Transportation; the program mandates every region have mass transportations. The BRT program seeks to help Mataram city, because the city transports service is low and they are less attractive; in addition, the number of private vehicles is high. The research objective to describe, identify and analyze problems in implementing BRT in Mataram. Moreover, this research employed a descriptive qualitative method; the researcher collected the data from interviews, observation, and document studies. Furthermore, this research used the qualitative data analysis interactive models. The findings reveal that BRT implementation in Mataram city was not optimally successful. This was due to long communication chain that must be carried out through socialization; the minimal socialization, unreached target groups, resources, and minimum BRT operational costs. The disposition displays a positive attitude; however, the commitment of BRT implementers is still low. In addition, the bureaucratic structure shows a limited pattern of relations between implementers; there are too many hierarchy levels which cause implementation inefficiency.